Local Frequency Restoration-Based Communication-Free Approach in Islanded Microgrids - Shamkhi, Ali; H. Jasim, Basil (Iraqi Journal for Electrical and Electronic Engineering, 2026)
Reducing the dependency of the control system on communication in the microgrid increases the reliability and flexibilityof an islanded microgrid. This paper presents a local secondary control approach to provide a fast response to powerchange and accurate frequency restoration. It is based on a control scheme that uses a secondary controller involvinga time-controllable parameter for a Low pass filter. The high value of the time-varying parameter is placed to satisfyexcellent performance regarding fast active power sharing, and the time-controllable parameter decreases after achievingpower-sharing based on a time protocol to ensure accurate steady-state frequency restoration. This paper also describesthe criteria for control parameter selection and stability analysis based on a precise modeling approach. The MATLABenvironment is used to simulate and test the proposed control scheme, and the results have been obtained that showthe validity and high performance of the proposed controller in terms of dynamic response to active power change andsteady-state restoration under different operation conditions.